From seropositivity to neurosyphilis: clinical spectrum and diagnostic classification in hospitalized neurology patients: a 16-year retrospective study - Duygu Özkan Yaşargün (Frontiers in Neurology, 2026)
Background Neurosyphilis remains a diagnostic challenge because of its heterogeneous neurological manifestations and the absence of a universally accepted diagnostic gold standard. Diagnostic categories such as confirmed and probable neurosyphilis may help stratify syphilis-seropositive patients according to clinical and cerebrospinal fluid findings. This study aimed to evaluate syphilis seropositivity among hospitalized neurology patients and to compare clinical, radiological, and discharge neurological characteristics across diagnostic groups. Methods This single-center retrospective observational study included adult patients hospitalized in the neurology ward between January 2010 and January 2026 who were identified as having positive serum treponemal serology. Patients were classified as confirmed neurosyphilis, probable neurosyphilis, or non-neurosyphilis seropositivity. Results Among 9,172 hospitalized neurology patients who underwent serum TPHA testing during the study period, 25 eligible patients with syphilis seropositivity were included in the analysis. Ten patients were classified as confirmed neurosyphilis, five as probable neurosyphilis, and ten as non-neurosyphilis seropositivity. Age, sex distribution, vascular ischemia on admission, HIV status, and CT angiography vascular involvement did not differ significantly among the groups. MRI findings suggestive of neurosyphilitic involvement and positive neurological examination at discharge differed significantly among the diagnostic groups (both p = 0.001). Pairwise comparisons showed that these differences were significant only between the confirmed neurosyphilis and non-neurosyphilis seropositivity groups. Conclusion Although syphilis seropositivity was uncommon among hospitalized neurology patients, a substantial proportion (60%) of seropositive individuals fulfilled the predefined criteria for confirmed or probable neurosyphilis. Our findings demonstrate that syphilis seropositivity should not be considered synonymous with neurosyphilis and highlight the importance of a comprehensive diagnostic evaluation integrating clinical presentation, cerebrospinal fluid findings, and neuroimaging. Syphilis testing remains a crucial component in the diagnostic evaluation of unexplained neurological syndromes in contemporary practice.